Pengembangan Modul Pembelajaran Pemeliharaan Sasis dan Pemindah Tenaga Kendaraan Ringan Untuk Program Keahlian Teknik Kendaraan Ringan - Ryohandoko, Harsono; Marsono, Marsono; Ichwanto, Muhammad Aris (Universitas Nahdlatul Ulama Blitar, 2024)
The purpose of this development is to produce a learning module for chassis maintenance and light vehicle power transfer for the light vehicle engineering expertise program. This module can provide practical guidance for students in carrying out maintenance and repairs. Students will be ready to enter the workforce after graduating with relevant skills. The development of teaching materials for Chassis Maintenance and Light Vehicle Power Transfer is based on a 4D development research model. Testing is carried out by media experts, material experts, small group tests and large group tests. The data collection instrument to determine the feasibility of developing chassis modules and light vehicle power transfers, using a questionnaire. Based on the results of the validation data, the percentage of eligibility is 3,676 for the validation of media experts and 3,583 for the validation of material experts, so that based on the criteria that have been set, the module meets the valid criteria. For the feasibility and effectiveness of the module, the results of the students' responses in the small group test were very feasible and for the large group trial, the results were obtained with a percentage (89% + 88%): 2 = 88.5%. Thus, the development of chassis modules and light vehicle power transfer is very feasible to be used as a learning medium on the chassis system elements and light vehicle power transfer Class XI SMK.